Judicial Non-Prosecution To Rape in Valdivia, Chile, 1840-1860. Proposal for a Debate over Social Violence and Its Approach in Regional Histories - Muñoz-Sougarret, Jorge Ernesto; Núñez, Paula Gabriela (Revista de Historia Social y de las Mentalidades, 2023)
This article exposes local forms of Patriarchal dynamics, based on rape trials, with a postulate to the understanding of Social Violence within Regional History. The entry point for the analysis will be the judicial practices and discourses, in a context of social, migratory and labour change. Through a study of documentary sources, uprising gender, ethnic and class discrimination against women. Being expressed in higher rates of criminalization towards them, meanwhile, reduced persecution of their male perpe- trators. Finally, this event, barely revealed by Regional History, is central to a revaluation of the discourses related to homogeneity and social inclusion at the local level.
Keywords: Sexual Violence; Iurisprudence; Regional History; Valdivia